Types and Classification of The Most Common Cereal-Like Annual and Perennial Weeds in Unused Agricultural Lands - Turdiyeva, Nilufar; Qalandarova, Maftuna; Murtazaev, Qobil; Yoldoshev, Abdulaziz Abdumalikovich; Togaeva, Dilnura Akbarovna (American Journal of Botany and Bioengineering, 2026)
This article identifies and classifies the most common annual and perennial weeds on unused agricultural land. Identifying and controlling weeds growing on unused land is important, as they are the primary source of overwintering, reproduction, and development of pests and diseases.